Dialektika Antara Akal dan Wahyu dalam Aqidah Filsafat Islam: Harmoni atau Konflik - sholeh, muh ibnu sholeh (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2023)
This study aims to find the dialectics between reason and revelation in the understanding of aqeedah in Islamic philosophy, to understand whether there is harmony  conflict  the interaction between reason and revelation in Islamic aqeedah, to formulate a more inclusive perspective in integrating this understanding with the development  science and thought. modern. The method used this study is library research method, literature studies obtained from various sources such as scientific journals, books, seminar papers, and other publications related to research topics both offline and online, data obtained analyzed using interactive qualitative model. This data analysis model consists data collection, data reduction, data presentation, and conclusion. The results research show that understanding  Islamic aqeedah, dialectic between reason and revelation reflects  complicated interaction between human rational abilities and divine guidance. Although reason contemplates reality of God with limitations, revelation as God's direct guidance has main authority in aqeedah. Islamic thinkers seek to combine reason and revelation through ijtihad and ta'wil, making them central elements the evolution religious thought. The interaction  reason and revelation in Islamic aqeedah raises challenges of harmony and conflict. There have been attempts to align the two with the view that true reason will support revelation, but sometimes reason and the teachings revelation are incompatible. An inclusive perspective in integrating reason and revelation  Islamic aqeedah with the development  modern science involves consideringtwo complementary, using concept  ijtihad for adaptation, taking into account the views omodern Muslim scholars, and encouraging dialogue between religion and science in order to create sustainable harmony.